Experimental investigation of heat conservation through novel flame shield arrangement for domestic LPG gas stove. (2022) - Gohil, Pankaj P.; Dwivedi, Gaurav; Shukla, Anoop Kumar; Verma, Puneet
Abstract: Gas burner plays a crucial role in any combustion systems. Thermal efficiency of conventional Liquefied petroleum gas (LPG) stove burner is not optimal. To recover the energy loss from a burner, a novel flame shield was developed based on heat conservation phenomenon for enhancing efficiency and producing less emission pollutant, which used for domestic and small-scale processing industries. Under the present study, an attempt has been made to investigate the efficiency, heat conservation, and emission products of LPG cooking stove for without and with flame shield method. The experimental test has been carried out based on the guideline of IS 4246:2002. Thermal efficiency was found of a conventional burner without flame shield is 66.27%. With usage of a flame shield, the maximum efficiency of 74.07% was found. Moreover, the maximum temperature gain and heat generation are increased by 2.1% and 3.0%, respectively. During the emission test, the CO2 increases from 0.9% to 3.8%, and NOx & HC are found less than without flame shield burner. The present study results indicate the better economic and environmental compatibility, to use the conventional gas stove burner with flame shield.